The candy house [compact disc, unabridged] - Egan, Jennifer (Egan, Jennifer. Goon Squad, 2022)
It's 2010. Staggeringly successful and brilliant tech entrepreneur Bix Bouton is desperate for a new idea. He's forty, with four kids, and restless when he stumbles into a conversation with mostly Columbia professors, one of whom is experimenting with downloading or 'externalizing' memory. Within a decade, Bix's new technology, Own Your Unconscious, that allows you access to every memory you've ever had, and to share every memory in exchange for access to the memories of others, has seduced multitudes. But not everyone.